Кооперативна діяльність подолянина Миколи Литвицького у період еміграції в Польщі (1921–1923 рр.) - Рекрут, В.; Костенко, О. (Краєзнавство, 2024)
На підставі виявлених архівних документів, аналізу публікацій сучасних дослідників та зарубіжної періодики досліджується кооперативна діяльність подолянина Миколи Олексійовича Литвицького у період вимушеної еміграції в Польщі (1921-1923 роках). Для реалізації зазначеної мети були застосовані біографічний, проблемно-хронологічний методи, а також методи історичної реконструкції. Розкрито основні здобутки М.О. Литвицького в розвитку національного кооперативного руху та відстоювання прав українського населення на тимчасово окупованій території Західної Волині. Висвітлено його участь у подіях щодо спроб відомих діячів української кооперації повернути власникам державні та кооперативні кошти, якими незаконно заволоділи функціонери зарубіжного «Об’єднання центральних українських спілок» (ОЦУКС). У наступних розвідках бачиться доцільним дослідити кооперативну та громадсько-політичну діяльність М.О. Литвицького під час проживання на території Чехословаччини (1923-1939). The article investigates cooperative activity of a Podolian Mykola Oleksiyovych Litvytskyi during the period of his forced emigration to Poland (1921-1923). The primary sources of this research include the newly discovered archival documents and materials of foreign periodicals, supplemented by analysis of publications by modern researchers. Biographical and problem-chronological methods as well as methods of historical reconstruction were used. The article discusses the main achievements of M.O. Litvytskyi in the development of the national cooperative movement and defense of the rights of Ukrainian population on the temporarily occupied territory of Western Volyn. Specific attention is given to the participation of M.O. Litvytsky, along with other renowned figures of Ukrainian cooperative movement, in the attempts to return state and cooperative funds that were illegally seized from the owners by the officials of the “Union of Central Ukrainian Associations”. We also argue that there is a need to further inquire into cooperative, social and political activity of M.O. Litvytskyi during the time of his residence in Czechoslovakia (1923-1939).